Silicon nanocrystal-based photonic crystal slabs with broadband and efficient directional light emission - Ondič, L; Varga, M; Pelant, I; Valenta, J; Kromka, A; Elliman, R G (Scientific reports, 2017)
Light extraction from a thin planar layer can be increased by introducing a two-dimensional periodic pattern on its surface. This structure, the so-called photonic crystal (PhC) slab, then not only enhances the extraction efficiency of light but can direct the extracted emission into desired angles. Careful design of the structures is important in order to have a spectral overlap of the emission with extraction (leaky) modes. We show that by fabricating PhC slabs with optimized dimensions from silicon nanocrystals (SiNCs) active layers, the extraction efficiency of vertical light emission from SiNCs at a particular wavelength can be enhanced ∼ 11 times compared to that of uncorrugated SiNCs-rich layer. More importantly, increased light emission can be obtained in a broad spectral range and, simultaneously, the extracted light can stay confined within relatively narrow angle around the normal to the sample plane. We demonstrate experimentally and theoretically that the physical origin of the enhancement is such that light originating from SiNCs first couples to leaky modes of the PhCs and is then efficiently extracted into the surrounding.